PEMIKIRAN HARUN NASUTION TENTANG KURIKULUM PENDIDIKAN TINGGI ISLAM - Huda, Nur (Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2013)
Harun Nasutions experience serves an office IAIN to regard its educational view. Largely Indonesian Islamic people, notably modernist Islamic thinking havent available one spots Harun Nasutions thinking flank educational. Islam education speaking, terminologicaling it dont despite 4 subject problems, first, to the effect Religion education; both of, Religion education material; third, Religion education method; and fourth, religion teacher quality. Component fourth upon point out education planning step islam in processes teaching and learning. To the effect education constitute first one element functioning as guidance in exhaustive education activity. Teaching that involves to learn, material and student gets orientation on intent. After intent education is formulated, second plan is arrange education material that terangkum systematically deep curriculum. Curriculum is arranged and at plots to base aim already being established.